A study on the impact of neoadjuvant therapy on molecular subtype conversion in breast cancer - Run-Ze Zhang; Dong Liu; Yuan Ke; Wen-Qi Cai; Lin-Hui Zheng; Chao-Yan Wu; Hai-Jun Yu (World Journal of Surgical Oncology)
Abstract Purpose The aim of this study was to examine molecular subtype conversions in patients who received neoadjuvant therapy. Methods and materials A retrospective analysis was performed on 316 patients who underwent neoadjuvant therapy at Zhongnan Hospital of Wuhan University between March 2017 and October 2024. The study included data from patients with confirmed pathological residual disease at the primary site post-surgery, alongside complete receptor status and detailed information on the neoadjuvant treatment regimen administered before and after therapy. Univariate and multivariate logistic regression analyses were employed to identify factors influencing molecular subtype heterogeneity before and after neoadjuvant therapy. Results Of the 316 patients who received neoadjuvant therapy and underwent repeated pathological biopsies, 84 (26.6%) achieved a pathological complete response (pCR). Among the remaining 232 patients with confirmed pathological residual disease after surgery, 85 (36.6%) exhibited conversion of molecular subtypes, with 45 cases (19.3%) leading to alterations in the treatment plan. In breast cancer patients undergoing neoadjuvant chemotherapy (NAC), particularly those with HR-positive tumors prior to NAC, those demonstrating favorable treatment responses on imaging, and those undergoing breast-conserving surgery, molecular subtype heterogeneity before and after NAC was more commonly observed. Conclusion Neoadjuvant therapy can induce molecular subtype heterogeneity in patients with invasive breast cancer. The identification of factors contributing to this heterogeneity may be associated with variations in biological markers of residual disease post-NAC, sampling discrepancies between core needle biopsy (CNB) and surgical specimens, or the selective mutagenic pressure exerted by chemotherapeutic agents.